Theoretical Investigation of Energetic and its Effect on Cd-Hg Amalgam (Journal of Nepal Physical Society, 2016)
The observed anomaly in properties of mixing of Cd-Hg alloys in the molten state is successfully explained on the basis of the quasi-lattice model. The thermodynamic functions such as free energy of mixing, heat of mixing, entropy of mixing and chemical activity of the constituent atom of the alloys and microscopic functions like concentration-concentration fluctuation in long wavelength limit and Warren-Cowley short range order parameter of the alloys have been computed within the frame work of presented model. Most of the computed values are in good agreement with the experimental data. The pair-wise interaction energies between the species of the melt are found to depend considerably on temperature. Theoretical analysis suggests that hetero-coordination leading to the formation of complex Cd2Hg is likely to exist but is of weakly interacting in nature.Journal of Nepal Physical Society Vol.3(1) 2015: 60-66